Evaluation of risk factors for Suicide Attempts in Turkey's East: A Five-Year Study - Bork, Turgay; Turkoglu, Abdurrahim; Atescelik, Metin; Tokgozl, Omer (Professional Medical Publications, 2021)
Objectives: Suicide attempt has different risk factors for each community. In the study we aimed to reveal the causes of suicide attempt in Turkey's Eastern part and to make suggestions to prevent suicide. Methods: For this study, 130 patients who were admitted to the Emergency Department of the University Hospital due to suicide attempt between January 2013 and December 2017 were included. Our University Hospital is the largest hospital in the East of Turkey. The data were obtained from hospital records and files of judicial investigations. Clinical progress records were obtained from the hospital archive. Investigation files were received from local judicial units. Results: Fifty six percent of the patients (n = 73) were female. 48% of female cases (n = 35) were married. There was major depressive disorder in 34% (n = 44) of the cases. Medicine taking was the most frequent suicide method with 63% (n = 82). The main reason for suicide was parental conflicts for female cases; and psychiatric and financial problems for males. Conclusion: Family therapy for married individuals would reduce suicide attempts in females. Psychiatric history is an important risk factor and it should be ensured that these patients are followed up regularly by the health institutions and their relatives. To prevent drug abuse, there should not be too much medicine in homes. If medicine is available at home, it should be kept in a safer environment.
Keywords: Forensic science; Risk factors; Suicide attempt